Genetic evaluation of physiological traits affecting water use efficiency in sunflower (Helianthus annuus L.): GENETIC EVALUATION OF PHYSIOLOGICAL TRAITS AFFECTING WUE IN SUNFLOWER - PRAFULL KUMAR,; S K DHILLON,; ABHINAV SAO,; HEMATH SAHU, (Journal of Oilseeds Research, 2014)
The present investigation was undertaken to evaluate 41 (26 restorer and 15 maintainer) genotypes of sunflower for physiological traits affecting water use efficiency under different environments. The traits studied were canopy temperature, leaf area index, photosynthetic rate and leaf water potential. Among the four stress treatments, W1 (control) irrigating during entire grown cycle yielded the maximum value for all the parameters, except canopy temperature, followed by W4, W3 and W2 (withholding of irrigations in different growth stages). In genotypes under study, the estimates of heritability and genetic advance were observed maximum for leaf area index followed by leaf water potential indicating the predominant additive gene effects for these parameters. Hence, these traits can be improved to a considerable extent by limited selection cycles. Estimation of GCV and PCV values were higher for leaf area index as compared to other traits indicating high genetic variability for leaf area index. Pooling of physiological and genetic parameters indicated that leaf water potential and photosynthetic capacity can be adopted for breeding of suitable crop varieties for changing climatic scenario.